Mapungubwe’s hinterland: excavations, ceramics and other material culture from Mutamba in the Soutpansberg - Antonites, Alexander (Southern African Humanities, 2019)
Mutamba is a 13th-century Iron Age settlement located in the Soutpansberg of South Africa and is contemporary with Mapungubwe, southern Africa’s earliest socially complex polity. This article presents information on excavations conducted in 2010 and 2011. The ceramic assemblage is considered in detail since it has implications for understanding the regional ceramic sequence and interactions at the site. The ceramic assemblage is dominated by vessels typologically attributable to the Mapungubwe facies, but also contains several vessels from the Eiland and Mutamba facies. This material is discussed in the context of the social and political backdrop of 13th-century South Africa, which shows that Mutamba formed part of the Mapungubwe polity’s dynamic hinterland. KEY WORDS: Mapungubwe, Mutamba, ceramics, Middle Iron Age, hinterland, interaction, Soutpansberg.